2014
DOI: 10.4102/pythagoras.v35i1.244
|View full text |Cite
|
Sign up to set email alerts
|

Number sense of final year pre-service primary school teachers

Abstract: Number sense studies have indicated that the development of number sense should be the focus of primary school mathematics education. The literature review revealed that learner performance is linked to teacher subject knowledge and that teachers’ confidence in doing and teaching mathematics influences the way they teach and their willingness to learn mathematics. This study was motivated by the poor performance of Namibian primary school learners in both national and international standardised assessment test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 15 publications
1
8
0
4
Order By: Relevance
“…She went on to say that 'many adults, including middle school teachers … and preservice teachers … struggle with the same concepts and hold the same primitive ideas and misconceptions as students do' (Lamon, 2007, p. 633). Courtney-Clarke and Wessels (2014) found that only 25% of preservice teachers in a study in Namibia could recognise the relative size of two common fractions in a comparison problem.…”
Section: Research On Proportional Reasoningmentioning
confidence: 95%
“…She went on to say that 'many adults, including middle school teachers … and preservice teachers … struggle with the same concepts and hold the same primitive ideas and misconceptions as students do' (Lamon, 2007, p. 633). Courtney-Clarke and Wessels (2014) found that only 25% of preservice teachers in a study in Namibia could recognise the relative size of two common fractions in a comparison problem.…”
Section: Research On Proportional Reasoningmentioning
confidence: 95%
“…Preservice mathematics teachers with good fraction sense usually have the skill and expertise needed to manage fractions. However, the fact is that most preservice teachers' skills in fraction sense remain low (Courtney- Clarke & Wessels, 2014;Iuculano & Butterworth, 2011;Lamberg & Wiest, 2014;Sengul & Gulbagci, 2012;Whitacre & Nickerson, 2016;Yaman, 2015;Yang, Reys, & Reys, 2009). Such skills are used not only when doing mathematical calculations, but also in daily life.…”
Section: Fraction Sensementioning
confidence: 99%
“…Research on cognitive obstacles related to fraction sense assignments is crucial, because it aids in understanding how these obstacles can be minimised. Meanwhile, most of the previous decade's research on preservice mathematics teachers related to fraction sense tests studied the fraction sense strategy used, the preservice teachers' low performance in the fraction domain, their understanding of representation and computation skills, their reasoning of fraction amounts, and their mental calculation (Courtney- Clarke & Wessels, 2014;Lemonidis, Tsakiridou, & Meliopoulou, 2018;Şengül, 2013;Son & Lee, 2016;Whitacre & Nickerson, 2016;Yang, Reys, & Reys, 2009). Consequently, a set of information is further required to acknowledge preservice teachers' cognitive obstacles on fraction sense tests.…”
Section: Introductionmentioning
confidence: 99%
“…Bu amaç doğrultusunda katılımcıların sayı hissinin ölçülmesine gerek duyulmuş ve bunun için bir literatür taraması yapılmıştır. Literatür taramasında öğretmen adaylarıyla yapılan çalışmalarda genellikle Yang (1995) tarafından geliştirip 6. ve 8. sınıf öğrencilerine uygulanan sayı hissi testinin kullanıldığı görülmüştür (Courtney-Clarke & Wessels, 2014;Tsao, 2004b). Bu testin katılımcıların seviyesine uygun olmadığı düşünülerek çalışma kapsamında "Sayı Hissi Testi" (SHT) olarak adlandırılan bir ölçme aracının geliştirilmesine karar verilmiştir.…”
Section: Veri Toplama Aracıunclassified